Iron Isotope Behavior During Melt‐Peridotite Interaction in Supra‐subduction Zone Ophiolite From Northern Tibet. Issue 2 (31st January 2020) - Zhang, Long; Sun, Wei‐dong; Zhang, Zhao‐Feng; An, Yajun; Liu, Fang
Abstract: Melt‐peridotite interaction has the ability to modify the δ 56 Fe of peridotite. However, iron isotopic fractionation during melt‐peridotite interaction is not well understood at present. In this study, we present high‐precision iron isotopic data for serpentinized and carbonated peridotite from the Yushigou supra‐subduction zone ophiolite in the North Qilian orogen of northern Tibet, to provide insights into iron isotope behavior during melt‐peridotite interaction in the mantle wedge. High‐Cr and high‐Al dunites coexist with harzburgite in the Yushigou ophiolite. The high‐Cr and high‐Al dunites were produced by interaction of peridotite with boninitic melt and tholeiitic melt, respectively. Serpentinization and carbonation have negligible influence on δ 56 Fe of the peridotite. The harzburgite mostly has δ 56 Fe ranging from −0.055 ± 0.029‰ to 0.056 ± 0.030‰, which overlaps with δ 56 Fe of abyssal peridotite. The high‐Al dunite is enriched in FeO, but it has δ 56 Fe (0.004 ± 0.034‰–0.083 ± 0.064‰) similar to the harzburgite. In contrast, the high‐Cr dunite displays a large range in δ 56 Fe from −0.173 ± 0.017‰ to 0.173 ± 0.057‰. Moreover, δ 56 Fe of the high‐Cr dunite is negatively correlated with its FeO content, which is ascribed to kinetic iron isotopic fractionation during melt‐peridotite interaction. Surprisingly, distinct iron isotope behavior during melt‐peridotite interaction recorded by the Yushigou peridotite can well explain the large variation of FeO and δ 56 Fe in abyssal peridotite and mantle wedge peridotite on a global scale. Key Points: High‐Cr and high‐Al dunites reflect contrasting melt‐peridotite interactions in supra‐subduction zone ophiolite from Northern Tibet δ 56 Fe of peridotite was not shifted during serpentinization and carbonation High‐Al dunite has limited δ 56 Fe that overlaps with harzburgite, while high‐Cr dunite has varying δ 56 Fe that inversely correlates with FeO